THE EFFECTIVENESS OF GROUP COUNSELING SERVICES WITH SYSTEMATIC DESENSITIZATION TECHNIQUES TO REDUCE PUBLIC SPEAKING ANXIETY IN JUNIOR HIGH SCHOOL STUDENTS - Egi Pratama Farida Aini; Nefi Darmayanti (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to determine the effectiveness of group counseling services with systematic desensitization techniques in reducing public speaking anxiety in junior high school students. This study uses a quantitative approach with the quasi-experiment one-group pre-test post-test design method. The participants of this study were grade VIII students of Junior High School in Medan, with a sample of 7 students. The sample was recruited using a purposive sampling technique based on the criteria of students who experienced high speech anxiety. The intervention was carried out through 4 group counseling sessions adjusted to systematic desensitization techniques. Data analysis using the Wilcoxon Signed Rank Test led to a decrease in the average score from 74.14 to 57.14 with an Asymp significance value. Sig (2-tailed) is 0.018. This proves that group counseling with systematic decentralization techniques can reduce public speaking anxiety in junior high school students.